Development and characterization of bouillo cube from blue swimming crab (Portunus pelagicus) processing wastes. - Jalbuna, Jana Ericka C.; Muegue, Mayflor (2023.)
Blue swimming crab (Portunus pelagicus) is a commercially significant crab species in the Philippines. Processing of this species generates substantial amount of wastes in the form of shells. The BSC processing wastes can be utilized in the production of high-value products in the form of seasonings, umami flavor enhancer powder, and crab-flavor flour, among others. This study aimed to optimize and characterize the bouillon cubes using BSC from processing wastes. The BSC processing wastes were subjected to heat treatment; 30 minutes boiling (30DB), 60 minutes boiling (60DB), and 10 minutes pressure cooking (10PC) then sundried, powdered, and produced as a bouillon cube. The produced cubes from the three treatments were subjected to microbial analysis including the enumeration of Aerobic Plate Count, Escherechia coli, and Salmonella detection to assess its microbiological safety. Sensory analysis was conducted for odor, flavor, general appearance, and general acceptability of bouillon cubes and soup with the developed bouillon cubes as flavoring. Physicochemical analyses were also done which include tests for water activity, solubility, bulk density, pH, and color analysis. The three treatments had APC below the standard microbiological limit and were also tested negative for both E. coli and Salmonella. The sensory analysis revealed that all bouillon cubes and soup have a crabby odor and flavor, have distinct umami taste, and with low detectable saltiness. The bouillon cubes exhibited low Aw (0.603±0.0), high solubility (78.89±3.16 to 81.13±1.50), high bulk density (0.57±0.02 ti 0.59±0.03), and a basic pH (8.54±0.01 to 8.57±0.01). The three treatments did not show any significant differences in the tests conducted, hence, the 30DB sample was identified as the most appropriate treatment for bouillon production because it is the cheapest, easiest, and most convenient to carry out producing equally safe and quality product. The 30DB sample was subjected to proximate and salt content analyses. It contains 30.01±0.16% ash, 5.52±0.13% moisture, 10.90±0.20% protein, 39.72±2.65% lipid, and 13.85±2.68% carbohydrate. The BSC cube has salt content of 13.73±0.49%. Based on the laboratory production scale, the individual price of one bouillon cube is Php 3.88. This study added variety to commercially existing BSC waste byproducts and bouillon cubes in the market. Most importantly, this study addresses Sustainable Development Goal 12, Responsible Production and Consumption by reducing ecological footprints through the utilization of the supposed waste from BSC processing into food products.
Thesis (Undergraduate, Bachelor of Science in Fisheries) Institute of Fish Processing, College of Fisheries and Ocean Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2023
Keywords: Crab; Portunus pelagicus